2023
DOI: 10.1039/d3cp01659e
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in catalytic dehydrogenation of propane over Pt-based catalysts

Abstract: Light alkenes are the key building blocks in chemical industry. As a propene on-purpose production technology, propane dehydrogenation has drawn par-ticular attention due to the growing demand for propene and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…According to the Arrhenius equation, the apparent activation energy for BDH on Pt(111) is calculated to be 0.69 eV. Many previous studies concerning light alkane dehydrogenation on Pt reported that at the beginning of the reaction, under-coordinated sites on the Pt catalyst would be preferentially blocked due to coke deposition, and a quick deactivation of the catalyst was often observed. , Consequently, the kinetics of the dehydrogenation reaction could be dominated to some extent by close-packed surfaces. The experimentally reported activation energies for light alkane dehydrogenation over supported Pt catalysts are summarized in Table S15.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Arrhenius equation, the apparent activation energy for BDH on Pt(111) is calculated to be 0.69 eV. Many previous studies concerning light alkane dehydrogenation on Pt reported that at the beginning of the reaction, under-coordinated sites on the Pt catalyst would be preferentially blocked due to coke deposition, and a quick deactivation of the catalyst was often observed. , Consequently, the kinetics of the dehydrogenation reaction could be dominated to some extent by close-packed surfaces. The experimentally reported activation energies for light alkane dehydrogenation over supported Pt catalysts are summarized in Table S15.…”
Section: Resultsmentioning
confidence: 99%
“…In the selection of the six promoter species investigated in our approach, we can draw on an ever increasing variety of single-promoter studies of Pt-based PDH catalysts in literature. , The reported elements with a potentially beneficial effect on the catalysis are alkali and earth-alkali metals like K or Ca, 3d transition metals like Mn, Fe, or Co, as well as main group metals like Al, Ga, or Sn. The increased selectivities observed upon the addition of alkali or earth-alkali metals are thereby mainly assigned to their potential to moderate the strong acid sites of the Al 2 O 3 support. ,, In contrast, the promoting effect of the metals is more discussed in terms of an improved Pt dispersion or the formation of intermetallic or oxidic compounds. ,,, Aiming to cover all of these suspected actions, we select two likely reducible (Fe, Co), two hardly reducible (Ga, Mn), and two moderating elements (K, Ca) as the promoters spanning the design space for a multipromoter PDH system. From the two known Oleflex promoters (Sn and K), the function of Sn is quite well understood in terms of Pt/Sn nanoalloy or intermetallic formation.…”
Section: Resultsmentioning
confidence: 99%
“…According to the model and in the considered range of concentrations, none of the tested promoter combinations is thus able to break the yield-deactivation trade-off suspected from single-promoter studies. ,,, In order to validate this important but slightly disappointing insight, we devise a further batch of experiments to specifically probe the tentative Pareto front. On the basis of the predicted performance descriptors, eight compositions are chosen accordingly, cf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic plastics, rubber, and fiber are the three major synthetic materials; their important raw material is propylene. , In addition, polypropylene protective equipment played an important role during the coronavirus disease . With the emergence of shale gas, propane dehydrogenation (PDH) has emerged as a significant alternative technique for producing propylene, as the conventional methods of producing the chemicalfluid catalytic cracking of heavy oil and steam cracking of naphthahave increasingly become insufficient to fulfill the growing demand. Cr-based and Pt-based catalysts are the main catalysts for PDH. Although the Cr-based catalyst is cheap, it is poisonous, and it is not environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%